Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1103/physrevd.62.044013
|View full text |Cite
|
Sign up to set email alerts
|

Gravitating dyons and the Lue-Weinberg bifurcation

Abstract: Gravitating t'Hooft-Polyakov magnetic monopoles can be constructed when coupling the Georgi-Glashow model to gravitation. For a given value of the Higgs boson mass, these gravitating solitons exist up to a critical value of the ratio of the vector meson mass to the Planck mass. The critical solution is characterized by a degenerate horizon of the metric. As pointed out recently by Lue and Weinberg, two types of critical solutions can occur, depending on the value of the Higgs boson mass. Here we investigate th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 17 publications
4
40
0
Order By: Relevance
“…This happens both in the low Higgs mass case, as was found by the original authors, as well as in the high Higgs mass case, as was shown by Brihaye, Hartmann and Kunzin [24] where the continuation of the original program has been carried out. Other studies connected with magnetic monopoles in the Einstein−Yang-Mills−Higgs theory can be mentioned: (i) The thermodynamical properties of these monopole black holes were further studied by Maeda et al [25,26,27] in the low Higgs mass case, and by Lue and Weinberg [22] for high Higgs mass; (ii) Ridgeway and Weinberg found the existence of non-spherically symmetric magnetic monopole configurations [28]; (iii) Dyonic solutions were found by Brihaye et al [29,30]; (iv) Monopole solutions in other theories were found, like in a Brans-Dicke theory [31], and in SU(3), SU (5), and SU(N) gauge theories [32,33,34].…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…This happens both in the low Higgs mass case, as was found by the original authors, as well as in the high Higgs mass case, as was shown by Brihaye, Hartmann and Kunzin [24] where the continuation of the original program has been carried out. Other studies connected with magnetic monopoles in the Einstein−Yang-Mills−Higgs theory can be mentioned: (i) The thermodynamical properties of these monopole black holes were further studied by Maeda et al [25,26,27] in the low Higgs mass case, and by Lue and Weinberg [22] for high Higgs mass; (ii) Ridgeway and Weinberg found the existence of non-spherically symmetric magnetic monopole configurations [28]; (iii) Dyonic solutions were found by Brihaye et al [29,30]; (iv) Monopole solutions in other theories were found, like in a Brans-Dicke theory [31], and in SU(3), SU (5), and SU(N) gauge theories [32,33,34].…”
Section: Introductionmentioning
confidence: 52%
“…Other studies connected with magnetic monopoles in the Einstein−Yang-Mills−Higgs theory can be mentioned: (i) The thermodynamical properties of these monopole black holes were further studied by Maeda et al [25,26,27] in the low Higgs mass case, and by Lue and Weinberg [22] for high Higgs mass; (ii) Ridgeway and Weinberg found the existence of non-spherically symmetric magnetic monopole configurations [28]; (iii) Dyonic solutions were found by Brihaye et al [29,30]; (iv) Monopole solutions in other theories were found, like in a Brans-Dicke theory [31], and in SU(3), SU (5), and SU(N) gauge theories [32,33,34]. Now, in a different context, the study of the Einstein-Maxwell system goes back to the origins of general relativity where Reissner in 1916 and Nordström in 1918 found the Reissner-Nordström solution (see [35] for the appropriate references), and Weyl studied axisymmetric gravito-electric vacuum systems in four dimensions [36].…”
Section: Introductionmentioning
confidence: 99%
“…More details on the method are given, e.g. in the Appendix of [30]. In this paper, the used mesh includes typically 10 3 points and the relative accuracy of the solutions is typically of the order of 10 −8 .…”
Section: Solutions and Their Propertiesmentioning
confidence: 99%
“…These come from the requirement of regularity of the origin [12]. Since particles are neither created nor destroyed during the time period of the simulation, we check that the total number of particles are conserved at each time step.…”
Section: )mentioning
confidence: 99%